Administrative, Financial, Criminal-Legal and Theoretical-Methodological Aspects of Regulating Social Relations - Leheza, Yevhen; Korniakova, Tatiana; Soldatkin, Igor; Rozmosh, Vladyslav; Opatsky, Roman (Jurnal Cita Hukum, 2022)
The purpose of the research is determined as theoretical, administrative, and civil law aspects of the regulation of social relations are defined. Main content. The article defines the means of social regulation, which include legal, moral, corporate, customs, etc. It has been proved that legal regulation of social relations is defined by the author as a purposeful action on people’s behavior and social relations with the help of legal (juridical) means. Methodology:  The methodological basis of the research is presented as comparative-legal and systematic analysis, formal-legal method, interpretation method, hermeneutic method, as well as methods of analysis and synthesis. Conclusions. It has been proved that since legal regulation is presented as social relations, legal regulation is determined by some objective and subjective factors. The following aspects of social relations have been resolved: level of economic development of the society; social structure of the community; level of maturity and stability of social relations; level of legal culture of citizens; level of certainty of the subject of social relations, means and methods of legal regulation etc.